DIALEKTIKA TRADISI DAN MODERNITAS: IJTIHAD MUHAMMAD IQBAL DALAM MEMBENTUK HERMENUTIKA HADIS - Hadziq, Abdulloh; Musahadi; Shodiq; Bistara, Raha; Rahmah, Mamluatur (Academic Journal of Islamic Principles and Philosophy, 2025)
This article aims to examine Muhammad Iqbal’s contribution to shaping a hermeneutical paradigm of hadith as a response to the stagnation of Islamic textual interpretation, which has often been rigid and ahistorical. Rooted in the realities of Islamic intellectual modernization and the influence of Western civilization, Iqbal proposes a hermeneutical approach to reconstructing hadith understanding in a more contextual, dynamic, and relevant manner for contemporary challenges. This study employs a qualitative method, utilising a library research approach, to explore Iqbal’s works and the thoughts of contemporary Islamic hermeneutics scholars. The main findings reveal that Iqbal not only distinguishes legal hadith from pre-Islamic traditions but also emphasizes the importance of dialogue between the text, its historical context, and modern audiences. Iqbal’s contribution lies in his assertion that hadith, as prophetic revelation, must be interpreted creatively and transformatively to produce a universal and humanistic form of Sharia. This study enriches hadith scholarship by positioning hermeneutics as a relevant interpretive method in the development of progressive Islamic thought.